Efficacy of Aqueous Plant Extracts in the Control of Downy Mildew (Peronospora variabilis) in Quinoa (Chenopodium quinoa) - Rolando Bautista-Gómez; Walter Mateu-Mateo; Miquer Aybar-Cordero; Victor Chávez-Centeno; Francisco Alejandro Espinoza-Montes (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Downy mildew caused by Peronospora variabilis is one of the main health problems affecting quinoa cultivation in the Andean region. The objective of this study was to evaluate the efficacy of aqueous extracts of garlic (Allium sativum), horsetail (Equisetum bogotense), and paico (Chenopodium ambrosioides) in reducing the severity of downy mildew and its effect on the yield of the Blanca Junín and Pasankalla quinoa varieties. The working solutions contained 10% of the crude extract. Foliar applications were made every 7 days, between 21 and 84 days after sowing. Using a randomized complete block split-plot design, severity, area under the disease progress curve (AUDPC), and relative efficacy (RE) of the treatment were quantified. The results revealed a significant interaction between variety and treatment (p < 0.05). Garlic extract in the Blanca Junín variety stood out as the best alternative for downy mildew control, considerably reducing AUDPC, increasing yield, and demonstrating greater RE (68.4%) compared to the synthetic fungicide metalaxyl. In the Pasankalla variety, because of its greater intrinsic tolerance, the impact of the extracts on yield was less pronounced. These findings position plant extracts, especially garlic extracts, as viable alternatives for the integrated management of downy mildew in quinoa crops, although it is recommended to validate their effectiveness in multiple campaigns that align with environmental sustainability and human health.